1998
DOI: 10.1046/j.1365-2133.1998.02409.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Langerhans cell apoptosis is inducedin vivoby nonanoic acid but not by sodium lauryl sulphate

Abstract: Exposure to irritants may cause chronic irritant contact dermatitis (ICD), characterized by irregular epidermal thickening and a predominantly dermal mononuclear cell infiltrate. The mechanisms involved, and why only certain individuals are affected, are not clearly understood. Different irritants may trigger different cellular and molecular interactions between resident skin cells and recruited inflammatory cells. In some individuals these interactions may become self-perpetuating resulting in persistent infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…It has been shown that SLS induces apoptosis in keratinocytes, but not in epidermal Langerhans cells (22). Furthermore, a study using an SLS‐induced cutaneous inflammation model, an immunotoxin induced apoptosis in activated macrophages (23).…”
Section: Death Mechanismmentioning
confidence: 99%
“…It has been shown that SLS induces apoptosis in keratinocytes, but not in epidermal Langerhans cells (22). Furthermore, a study using an SLS‐induced cutaneous inflammation model, an immunotoxin induced apoptosis in activated macrophages (23).…”
Section: Death Mechanismmentioning
confidence: 99%
“…Sodium lauryl sulfate (SLS) is an irritant of the corrosive type and may-even in subclinical reactions-result in impairment of the water barrier function of the skin (Tupker et al, 1997), whereas nonanoic acid (NON) induces irritancy of the noncorrosive type-i.e., the water barrier is not always affected (Fullerton et al, 2002;Wahlberg and Lindberg, 2003). The diversity of skin reactions caused by SLS and NON is recognized clinically (Reiche et al, 1998), instrumentally (Agner and Serup, 1989), histopathologically and ultrastructurally (Willis et al, 1989;Forsey et al, 1998), immunohistochemically (Lindberg et al, 1991), and transcriptionally (Grangsjo et al, 1996). Moreover, treatment responses may be different for cumulative skin exposure to SLS compared with NON (Andersen et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…When SDS was applied to the 3D reconstructed epidermis prepared with T‐nC‐HDK1, we observed chromatin condensation (Figure C‐E) that was characteristic of apoptotic cells . These results were similar to a previous study that showed that SDS induced apoptosis in keratinocytes in human skin . However, further studies are required to determine whether the chromatin condensation we observed in this study depends on apoptosis.…”
Section: Discussionmentioning
confidence: 99%